2008
DOI: 10.1080/01443610802149954
|View full text |Cite
|
Sign up to set email alerts
|

Is transvaginal ultrasound a worthwhile investigation for women undergoing vaginal hysterectomy?

Abstract: Vaginal hysterectomy (VH) is the definitive surgical management for uterine prolapse. It is also the preferred route for other pelvic pathology where a hysterectomy is warranted, as it is associated with lower complication rate and faster recovery time. The aim of this study was to determine the usefulness of transvaginal ultrasound scan (TVS) as an investigation prior to vaginal hysterectomy. A total of 103 patients were reviewed over 1 year. Associated gynaecological pathology was found in 46.6% of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Also the absence of ovarian cancer in our series is consistent with previous reports underlining the usefulness of transvaginal ultrasonography as an investigation prior to prolapse surgery [2,17]. In a study that evaluates the usefulness of transvaginal ultrasonography prior to vaginal hysterectomy Srikrishna et al found gynecological pathology in 46.6% of patients and changed the planned management in 2.9% of cases due to large fibroids and ovarian cysts [18]. The strengths of our study come from the single institution data with all cases evaluated with transvaginal ultrasoud, cervical cytology and endometrial sampling in cases of necessity.…”
Section: Discussionsupporting
confidence: 80%
“…Also the absence of ovarian cancer in our series is consistent with previous reports underlining the usefulness of transvaginal ultrasonography as an investigation prior to prolapse surgery [2,17]. In a study that evaluates the usefulness of transvaginal ultrasonography prior to vaginal hysterectomy Srikrishna et al found gynecological pathology in 46.6% of patients and changed the planned management in 2.9% of cases due to large fibroids and ovarian cysts [18]. The strengths of our study come from the single institution data with all cases evaluated with transvaginal ultrasoud, cervical cytology and endometrial sampling in cases of necessity.…”
Section: Discussionsupporting
confidence: 80%
“…The precolpocleisis exam should include a careful speculum exam with visual inspection of the cervix and vagina followed by palpation of the entire vagina [ 8 ] as well as a bimanual and rectal exam in addition to cervical cytology, transvaginal ultrasound, and endometrial sampling when indicated [ 11 ]. The role of transvaginal ultrasound as a preoperative tool in the assessment of gynecologic pathology has been suggested by several authors [ 11 , 12 ]. There is a 1.1% risk of missing an early endometrial carcinoma in postmenopausal women when preserving the uterus for prolapse surgery and thus a preoperative ultrasound is recommended in all cases followed by endometrial sampling when indicated [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…18 Another study of 49 women correlated the size of the nongravid uterus measured by ultrasound with bimanual examination before hysterectomy and postoperative surgical pathology specimens. 18 Another study of 49 women correlated the size of the nongravid uterus measured by ultrasound with bimanual examination before hysterectomy and postoperative surgical pathology specimens.…”
Section: Preoperative Evaluationmentioning
confidence: 99%